Inhibition of substrate synthesis as a strategy for glycolipid lysosomal storage disease therapy. - Platt, F; Jeyakumar, M; Andersson, U; Priestman, D; Dwek, R; Butters, T; Cox, T; Lachmann, R; Hollak, C; Aerts, J; Van Weely, S; Hrebícek, M; et al. (2001)
The glycosphingolipid (GSL) lysosomal storage diseases are caused by mutations in the genes encoding the glycohydrolases that catabolize GSLs within lysosomes. In these diseases the substrate for the defective enzyme accumulates in the lysosome and the stored GSL leads to cellular dysfunction and disease. The diseases frequently have a progressive neurodegenerative course. The therapeutic options for treating these diseases are relatively limited, and for the majority there are no effective therapies. The problem is further compounded by difficulties in delivering therapeutic agents to the brain. Most research effort to date has focused on strategies for augmenting enzyme levels to compensate for the underlying defect. These include bone marrow transplantation (BMT), enzyme replacement and gene therapy. An alternative strategy that we have been exploring is substrate deprivation. This approach aims to balance the rate of GSL synthesis with the impaired rate of GSL breakdown. The imino sugar N-butyldeoxynojirimycin (NB-DNJ) inhibits the first step in GSL biosynthesis and has been used to evaluate this approach. Studies in an asymptomatic mouse model of Tay-Sachs disease have shown that substrate deprivation prevents GSL storage in the CNS. In a severe neurodegenerative mouse model of Sandhoff disease, substrate deprivation delayed the onset of symptoms and disease progression and significantly increased life expectancy. Combining NB-DNJ and BMT was found to be synergistic in the Sandhoff mouse model. A clinical trial in type I Gaucher disease has been undertaken and has shown beneficial effects. Efficacy was demonstrated on the basis of significant decreases in liver and spleen volumes, gradual but significant improvement in haematological parameters and disease activity markers, together with diminished GSL biosynthesis and storage as determined by independent biochemical assays. Further trials in type I Gaucher disease are in progress; studies are planned in patients with GSL storage in the CNS.